Enhanced 3D-databases: A fully electrostatic database of AM1-optimized structures - Beck, Bernd; Horn, Anselm; Clark, Timothy; et al. (Journal of Chemical Information and Computer Sciences, 1998)
In a feasibility study, a single conformation 3D version of the Maybridge database (53 471 compounds) has been produced using geometries optimized with AM1 semiempirical MO-theory. The database entries include full electrostatic information within the NAO-PC model and can be used to generate spectroscopic and physical properties using established QSPR models. The data were generated from the original database using custom cleanup software to remove database inconsistencies and, for instance, to isolate the "interesting" ion of ion pairs, 2D to 3D conversion using CORINA and subsequent geometry optimization using VAMP. The complete geometry optimization run was carried out in less than 15 h elapsed time on a Silicon Graphics Origin 2000 with 126 processors. The total failure rate for the structure cleanup, 2D to 3D conversion, and geometry optimization steps was around 1%.